How E-Wom Influence Purchase Intention Mediated by Trust and Brand Awareness: Case on Generation X in Indonesia - Arifin, Rendy; Syah, Tantri Yanuar Rahmat (School of Business, Bogor Agricultural University (SB-IPB), 2023)
nformation spreads rapidly through social media, with a steady increase in social media users in Indonesia each year. This presents an important concern for marketers, particularly in the automotive industry, which has experienced growth in car sales in 2021. Information disseminated between social media users, known as electronic word-of-mouth (e-WOM), is believed to have an impact on consumers' purchase intentions. Therefore, this research aims to examine the influence of e-WOM on social media affects the purchase intention of a car in Indonesia. This study uses a quantitative research approach with the application of Structural Equation Model (SEM) method. Data collection is conducted with the purposive sampling technique, targeting Generation X respondents in Indonesia who actively use social media and feels interested to buy a car. The questionnaire is distributed via Google Forms, and data analysis is conducted by SPSS 24 and SmartPLS 3. From 119 respondents, trust and brand awareness emerge as the key factors that increase purchase intention for a car in Generation X. Additionally, trust and brand awareness act as mediators between e-WOM and purchase intention, because e-WOM does not directly impact purchase intention. In addition, this study does not provide evidence supporting the moderating role of price. In conclusion, car marketers in Indonesia should effectively manage the spread of e-WOM information on social media platform.s This information has the potential to enhance consumer brand trust and awareness, influencing the emergence of their purchase intentions. Keywords: brand awareness, e-wom, generation x, purchase intention, social media